Difference in Diet and Water Quality Influencing the Growth of the Newly Introduced Penaeus merguiensis Larva Culture - Mostafa Imhmed Ighwerb; Johannes Hutabarat; Ervia Yudiati; Rudhi Pribadi (Marine Science Department Diponegoro University, 2021)
The water quality found on the surface is usually better than that accumulated at the seabed and more bottomless sea. When recycled, water usually brings many materials along the path, all the way to reaching its end. Water quality varies from place to place, season, and different types of rock and soil it passes through also influences the possessed quality. By employing Penaeus merguiensis larvae produced by the Marine Research Center Hatchery owned by Jepara's government, this study analyzes varying effects in three nominal salinities (28, 32, and 36 ppt) and types of diets (Diet A: 100% live feed; Diet B: 100% FRIPPAK; Diet C: a combination of Diet A and Diet C, 50 % each) and finds the optimum water quality parameters such as dissolved oxygen, pH, and temperature on the growth of the newly introduced Penaeus merguiensis larvae. The results show that two nominals of water salinities (28 and 32 ppt) with Diet A works well, supporting the growth from most Zoea to Postlarvae-1: Zoea-1 at 28 ppt with Diet A; Zoea-2 at 32 ppt with Diet A; Zoea-3 at 32 ppt with Diet A; Mysis-1 at 28 ppt with Diet A; Mysis-2 at 28 ppt with Diet C; Mysis-3 at 28 ppt with Diet A; Postlarva-1 at 28 ppt with Diet A. All shrimp prefers temperature ranging from 31-32.4 °C with dissolved oxygen of 4.9-5.74 ppm and pH 7.0-8.1.